At the Crossroads. Management and Business History in Entrepreneurship Research - Águeda Gil; Ricardo Zozimo; Elena San Román; Sarah Jack (Journal of Evolutionary Studies in Business, 2016)
Recent calls for a historic turn in organization studies offer the opportunity to relaunch dialogue between management and business history research. Focusing on the specific domain of entrepreneurship research, this article illustrates the potential of mutual contributions from management and business history. In doing so, it demonstrates how historical approaches strongly influenced the early theoretical developments within entrepreneurship and demonstrates the potential to contribute to future scholarly debates. In sum, this article brings closer together business history and management studies stressing that their different perspectives and approaches are very valuable to enriching entrepreneurship research.